Knowledge, attitudes and practices towards lung cancer among adults in KwaZulu-Natal, South Africa: a cross-sectional survey - S. B. Dlamini; B. Sartorius; T. G. Ginindza (AOSIS, 2022)
Background.  Lung cancer remains the number one cause of cancer mortality estimated at 1.8 million deaths. There are limited studies in resource poor countries regarding knowledge, attitudes and practices towards lung cancer. Objective. This study aimed to describe the knowledge, attitudes and practices regarding lung cancer in selected communities in KwaZulu-Natal, South Africa. Methods. An observational, analytic cross-sectional study design was conducted using a standardized questionnaire. A stratified random cluster sampling method was applied across five communities. A regression model was developed to identify the predictors of the level of knowledge. Results. About 59.9% (95% CI 52.0 - 67.3) of the participants reported to have heard of lung cancer. The mean knowledge score was 41.8% (95% CI 35.7 - 47.9%). Coughing blood was the most recognized symptom (61.0%, 95% CI 52.1 - 69.1). About 17% (95% CI 14.7 - 21.5) of participants reported to be smokers. Many respondents reported that they would go to a health centre or clinic in case they were coughing blood (72.4%, 95% CI 93.9 - 79.5). Less than 10% (95% CI 3.9 - 8.1) of participants was screened for lung cancer at the time. Gender, history of working in the chemicals industry, screening for lung cancer, and time taken to seek health care when sick were significant predictors of lung cancer knowledge. Conclusions.  Public health interventions should be explored to increase the levels of community awareness regarding lung cancer, particularly focusing on the importance of screening, early diagnosis and treatment.